Metrology for 5G and emerging wireless technologies - Loh, Tian Hong (IET telecommunications series, 2021)
This book is the first to focus on metrology for current and future wireless communication technologies. It presents an overview of metrological capabilities and testbeds developed under several UK, EU and international programmes as well as other international efforts for 5G and beyond